EXPERIMENTAL JUSTIFICATION FOR THE CLOSURE OF WOUND DEFECTS USING COMPOSITE COLLAGEN IN DIABETIC FOOT SYNDROME - Malikov Nodirbek Muzaffar o‘g‘li; Ergashov Ulug‘bek Yusufjanovich; Atadjanova Safina Azizbekovna (Scholars Digest Publishing, 2024)
Objective: To treat wounds caused by alloxan-induced diabetes under experimental conditions using a modern topical agent. Materials and methods: Healthy rats were selected for the experiment. Experimental studies were conducted on 155 male white rats weighing 150-200 g, housed in the vivarium of the Tashkent Medical Academy (TMA). Results: The use of this type of collagen prevented endogenous intoxication, and the high efficacy of the new topical agent was demonstrated. It proved effective in treating systemic intoxication and mechanical injuries in diabetic rats, leading to its recommendation for use in the treatment of patients with diabetic foot defects. Conclusions: Collagen with quercetin helped to understand the molecular factors involved in the development of diabetic foot syndrome, the pathogenetic mechanisms of endothelial dysfunction, and the processes of neoangiogenesis in the progression of the pathology.
Keywords: composite collagen, diabetic foot, quercetin, alloxan, experiment.